The hope of Israel the resurrection of Christ in the acts of the Apostles - Crowe, Brandon D. (Grand Rapids Baker Academic, 2020)
This study on Jesus's resurrection in Acts explores the historical, theological, and canonical implications of the resurrection in early Christianity.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books